School Readiness of Ummul Habibah Pre-School Students in Klambir V Kebun Village measured by the Nijmeegse Schoolbekwaamheids Test (NST) - Munisa Munisa; Rita Nofianti; Naya Rama Andini (International Journal of Multilingual Education and Applied Linguistics, 2024)
The reason readiness matters are that children who are prepared for school will advance in their development. The term "school readiness" describes a child's ability to transition to school smoothly and successfully. Even among children of the same age, there are differences in a child's school readiness. The problem in today's society is that many parents think that the only aspect needed for children to enter primary school is the cognitive aspect, which includes the ability to write, read and count. The impact of this view is that many parents demand their children to be able to read, write and calculate after graduating from kindergarten because of the intense competition among favorite schools. In this study, a qualitative descriptive technique was used. The research was conducted at Ummul Habibah Pre-School, Klambir V Kebun village, Deli Serdang Regency. In this study, data collection methods used interview and observation. The three-pronged approach were used as data analysis—data reduction, data presentation, and conclusion drawing or verification. Based on the data result, the 5 children who were given the CPM and NST tests, had readiness to join the next school level. These children have adequate absorption and intelligence in solving problems and have adequate concentration. One of the intelligence factors in children's readiness to enter primary school can be explained that children who have high intelligence tend to have intelligent behavior in making decisions and solving problems. The results in the study illustrate that students who have high problem-solving test scores also have high scores in completing the readiness test (NST) and vice versa for students whose low problem solving test scores are also followed by low scores.